Inositol 1, 4, 5‐trisphosphate receptor determines intracellular Ca2+ concentration in Trypanosoma cruzi throughout its life cycle. Issue 12 (14th October 2016) - Hashimoto, Muneaki; Doi, Motomichi; Kurebayashi, Nagomi; Furukawa, Koji; Hirawake‐Mogi, Hiroko; Ohmiya, Yoshihiro; Sakurai, Takashi; Mita, Toshihiro; Mikoshiba, Katsuhiko; Nara, Takeshi
Abstract : Regulation of intracellular Ca 2+ concentration ([Ca 2+ ]i ) is vital for eukaryotic organisms. Recently, we identified a Ca 2+ channel (TcIP3 R) associated with intracellular Ca 2+ stores in Trypanosoma cruzi, the parasitic protist that causes Chagas disease. In this study, we measured [Ca 2+ ]i during the parasite life cycle and determined whether TcIP3 R is involved in the observed variations. Parasites expressing R‐GECO1, a red fluorescent, genetically encoded Ca 2+ indicator for optical imaging that fluoresces when bound to Ca 2+, were produced. Using these R‐GECO1‐expressing parasites to measure [Ca 2+ ]i, we found that the [Ca 2+ ]i in epimastigotes was significantly higher than that in trypomastigotes and lower than that in amastigotes, and we observed a positive correlation between TcIP 3 R mRNA expression and [Ca 2+ ]i during the parasite life cycle both in vitro and in vivo . We also generated R‐GECO1‐expressing parasites with TcIP3 R expression levels that were approximately 65% of wild‐type (wt) levels (SKO parasites), and [Ca 2+ ]i in the wt and SKO parasites was compared. The [Ca 2+ ]i in SKO parasites was reduced to approximately 50–65% of that in wt parasites. These results show that TcIP3 R is the determinant of [Ca 2+ ]i in T. cruzi . Since Ca 2+ signaling is vital for these parasites, TcIP3 R is a promising drug target for Chagas disease. Abstract : Regulation of intracellular Ca 2+ concentration ([Ca 2+ ]i ) is vital for eukaryotic organisms. Recently, we identified a Ca 2+ channel (TcIP3 R) associated with intracellular Ca 2+ stores in Trypanosoma cruzi . In this study, we measured [Ca 2+ ]i during the parasite life cycle and determined whether TcIP3 R is involved in the observed variations, and show that TcIP3 R is the determinant of [Ca 2+ ]i in T. cruzi, indicating that TcIP3 R is a promising drug target for Chagas disease.